치과위생사의 자아존중감과 윤리적 성향과의 관련성 - 이세정; Se Jung Lee; 한경순; Gyeong Soon Han (Chiwisaeng gwahakoeji, 2012)
The aim of this study was to the self-concept and ethical propensity of dental hygienists. The subjects of this study were 748 dental hygienists from January 23 to March 30, 2012. Data were analyzed with t-test, one-way ANOVA, Pearson``s correlation, and stepwise multiple regression analysis SPSS 19.0. The average score of self-concept was 3.44 points in dental hygienists. The self-concept scores were higher in absolutists (3.53 points) and situationists (3.51 points) than subjectivists (3.35 points) and exceptionists (3.35 points) in the ethical types. The self-concept Influence factors were idealism, relativism, job satisfaction level, and annual salary. In order to help dental hygiene students adopt to rapidly changing society, the university should make efforts to develop a curriculum and program for improving self concept and ethical propensity.